DIPG-68. ONCOGENIC MECHANISMS OF H3.3 K27M IN A SPONTANEOUS DIPG MOUSE MODEL. Issue 2 (22nd June 2018) - Larson, Jon; Kasper, Lawryn; Paugh, Barbara; Wu, Gang; Jin, Hongjian; Fan, Yiping; Kwon, Chang-Hyuk; Finkelstein, David; Silveira, Andre; Xu, Raymond; Zhu, Xiaoyan; Zhang, Junyuan; et al.
Abstract: Diffuse intrinsic pontine gliomas (DIPG) are deadly childhood brainstem tumors that comprise approximately half of all pediatric high-grade gliomas (HGG). Recurrent, clonal somatic mutations in histone H3 are a molecular hallmark that distinguish genetic mechanisms underlying pediatric and adult HGG, and indicate a strong link between epigenetic dysfunction and pediatric brain tumorigenesis. H3K27M mutations found in nearly 80 percent of DIPGs and over half of non-brainstem HGGs occurring in thalamus or other midline structures, induce a dominant loss of genome-wide H3K27me3. To study this mutation in the developing mammalian brain and investigate how it contributes to gliomagenesis, we generated conditionally activated, epitope-tagged knock-in mice to express K27M or non-mutated H3.3 proteins from the endogenous H3f3a locus. Untransformed embryonic neural precursor cells expressing H3.3K27M demonstrated H3K27me3 loss and a significant growth advantage in vitro with brain region-specific, stage-dependent expression and epigenetic signatures. DIPGs frequently harbor genetic alterations in TP53 and PDGFRA in addition to H3.3K27M, and mice with induced brain-specific Trp53 deletion plus mutated PDGFRA V544ins expression developed spontaneous HGG in vivo . Induction of H3.3K27M significantly accelerated PDGFRA V544ins ; Trp53 knockout HGG formation involving the brainstem. Importantly, non-mutated H3.3 epitope-tagged protein did not affect tumor burden or latency. H3.3K27M tumors recapitulate characteristics observed in human DIPG including histopathological features, strong nuclear K27M expression and robust loss of H3K27me3 throughout the tumors. Using RNA-seq and ChIP-seq, we relate the genetic, epigenetic and transcriptional landscapes of these models to primary pediatric DIPG to help identify their developmental origins and oncogenic mechanisms downstream of histone H3.3K27M.